A model of the UV skin dose distribution in paediatric whole-body phototherapy. (16th September 2021) - Coleman, AJ; Aneju, G A; Freeman, P; Fedele, F
Abstract: The radiance equation is applied in this study to model the ultraviolet (UV) radiation dose distribution over the skin in paediatric and adult patients treated in a whole-body phototherapy cabin. This approach extends a previously published model of UV radiation dose based on thermal radiation exchange between surfaces (Coleman et al 2020 Biomed. Phys. Eng. Express 6 055023). The new model makes it feasible to predict the distribution of UV irradiance over the head, trunk and legs in patients of varying height. The modelled irradiance distributions to directly lamp-facing skin surfaces agree to within 10% of those measured in simulated clinical paediatric treatments in a modern narrowband UVB treatment cabin. For a 10 year old (of height 1.36 m), for example, the model and the clinical measurements both show a UV radiation dose to the face that is around 25% more than that in an adult (of height 1.8 m). The dose to the crown of the head of a 10 year old is both predicted and measured to be more than double that of an adult. The automated dosimetry system, incorporated within the treatment cabin, is also predicted to overestimate irradiance to the body by between 10% and 25% in patients aged between 10 and 4 years (height 1.36–1.0 m). The value of the model and its implications for paediatric whole-body UV treatment in adult-size whole-body treatment cabins are considered.